Kajian Literatur Tentang Hubungan Pendidikan Multikultural Dan Sikap Toleransi Siswa - Nizam, Syahrul; Ubabuddin, Ubabuddin (ILJ: Islamic Learning Journal, 2025)
This study uses the literature study method to analyze the role of multicultural education in enhancing students' tolerance attitudes in Sambas Regency. The literature research method gathers data from various primary and secondary sources, such as books, journals, and research reports, relevant to the topic being studied. The data is analyzed descriptively and interpretively to provide a deep understanding of the management of multicultural learning and its impact on students' tolerance attitudes. The results show that, although education in Sambas Regency has made significant progress, there are still challenges in developing lesson plans that cater to students' needs. Therefore, multicultural education can serve as a solution to improve the quality of learning and assist teachers in developing inclusive materials and methods. Multicultural education plays a strategic role in teaching students to appreciate differences and create a harmonious and inclusive environment. Furthermore, this education can reduce discrimination, enhance students' social skills, and raise higher cultural awareness.